Mycorrhizal Fungal Application in Citrus Plants - Wu, Qiang-Sheng; Zou, Ying-Ning (Mycorrhizal Fungal Application in Citrus Plants, 2021)
In recent years, the interaction between citrus and arbuscular mycorrhizal fungi (AMF) has become an important research direction and an international hotspot in the study of citrus plants. A large number of pot studies have fully shown that AMF inoculation strongly stimulated the growth performance of citrus plants and accelerated the uptake of nutrients in the soil, especially P, Fe, Cu, K, Ca, etc. On the other hand, AMF also induce the occurrence of root hairs in citrus plants under low P condition, indicating that mycorrhizal fungi and root hairs synergistically promote the absorption of nutrients. In addition, Prof. Qiang-Sheng Wu, from Yangtze University, led a team that carried out a lot of constructive work around the various mechanisms of arbuscular mycorrhizas in enhancing drought tolerance in citrus. The inoculation experiments with AMF in the field have been attempted. As a result, this book provides a systematical overview of mycorrhizal roles on citrus, an analysis of the population diversity of mycorrhizal fungi on citrus rhizosphere, and the propagation of indigenous mycorrhizal fungi. The book also summarizes the inoculation method of potted citrus at the nursey, the sterilization method of substrates, the field evaluation of applied AMF, and the field management of citrus mycorrhizas. This book can act as a technical reference for the application of mycorrhizal fungi in citrus. It also provides some field examples for mycorrhizal research. This book can be served as a theoretical textbook and reference book for researchers of pomology and citrus, as well as for researchers and graduate students working in mycorrhizas.